Comparative Genomic Analyses of the Human NPHP1 Locus Reveal Complex Genomic Architecture and Its Regional Evolution in Primates. - Yuan, Bo; Liu, Pengfei; Gupta, Aditya; Beck, Christine R; Tejomurtula, Anusha; Campbell, Ian M; Gambin, Tomasz; Simmons, Alexandra D; Withers, Marjorie A; Harris, R Alan; Rogers, Jeffrey; Schwartz, David C; et al. (PLoS Genet, 2015)
Many loci in the human genome harbor complex genomic structures that can result in susceptibility to genomic rearrangements leading to various genomic disorders. Nephronophthisis 1 (NPHP1, MIM# 256100) is an autosomal recessive disorder that can be caused by defects of NPHP1; the gene maps within the human 2q13 region where low copy repeats (LCRs) are abundant. Loss of function of NPHP1 is responsible for approximately 85% of the NPHP1 cases-about 80% of such individuals carry a large recurrent homozygous NPHP1 deletion that occurs via nonallelic homologous recombination (NAHR) between two flanking directly oriented ~45 kb LCRs. Published data revealed a non-pathogenic inversion polymorphism involving the NPHP1 gene flanked by two inverted ~358 kb LCRs. Using optical mapping and array-comparative genomic hybridization, we identified three potential novel structural variant (SV) haplotypes at the NPHP1 locus that may protect a haploid genome from the NPHP1 deletion. Inter-species comparative genomic analyses among primate genomes revealed massive genomic changes during evolution. The aggregated data suggest that dynamic genomic rearrangements occurred historically within the NPHP1 locus and generated SV haplotypes observed in the human population today, which may confer differential susceptibility to genomic instability and the NPHP1 deletion within a personal genome. Our study documents diverse SV haplotypes at a complex LCR-laden human genomic region. Comparative analyses provide a model for how this complex region arose during primate evolution, and studies among humans suggest that intra-species polymorphism may potentially modulate an individual's susceptibility to acquiring disease-associated alleles.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Comparative Genomic Hybridization; Evolution, Molecular; Gene Dosage; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Haplotypes; Humans; Kidney Diseases, Cystic; Membrane Proteins; Primates